Deposition of Suspended Magnetite in High Temperature High Pressure Boiler Environments. (24th July 2015) - Raman, Balaji; Hall, Derek M.; Shulder, Stephen J; Caravaggio, Michael; Lvov, Serguei N.
Abstract : Suspended magnetite particles in boiler waters were found to deposit in orifice headers, impeding flow and causing inefficiencies and boiler tube failures from overheating. Particle interactions due to the zeta potential developed on the colloidal magnetite particles could also be a factor in deposition. To study the mechanism behind the deposition of suspended magnetite on stainless steel, a high temperature high pressure electrophoretic deposition cell with provisions to test 304 stainless steel substrates has been developed. The tests, conducted at pH25 °C of 9.3 in simulated boiler conditions in terms of temperature, pressure and water chemistry. The deposition was monitored using in-situ Electrochemical Impedance Spectroscopy (EIS) and post-test surface analyses were carried out on the substrate. The results of the tests concurred with the theory on oxide particle behavior in aqueous systems and colloidal stability. The specific conditions in the boiler that favor deposition have been successfully replicated.